Green Human Resources: Strategies for a Sustainable Future - Kaymakcı, Serap (Zenodo, 2025)
The analysis of the consequences of the Industrial Revolution, which affected various aspects globally including the economy, society and the environment starting with the late 18th century in England, has been in the limelight for quite some time. The exploitation of fossil fuels caused Global warming and greenhouse gases degeneration. Other than that, large scale farming practices that involve the application of heavy pesticides have worsened the situation. The environmental degradation that originated in this time period became the subject of scientific investigation in the twentieth century. Green Human Resource Management (GHRM) is a progressively management principles that embodies all imp0rt corporate social responsibility in offering Human Resources Services to the organization. GHRM transforms conventional HR functions, like, recruiting, training, evaluating performance etc, into green variants in a bid to recruit eco-friendly personnel and prepare them for achieving organizational environmental objectives. These actions assist corporations in meeting their obligations towards the external environment and in achieving their corporate social responsibility (CSR) objectives. The successful application of GHRM strategies allows organizations to reach their sustainability objectives, achieve the competitive advantage, and generate economic benefits. Employee eco-centrism and effectiveness of the management of GHRM strategies, as practice underpinned by use of information technology. Therefore, the aim of this study is to provide information about green human resources in the context of global climate change, sustainability and future trends.
Keywords: human resources; green; sustainable